2020
DOI: 10.9734/jenrr/2020/v4i230122
|View full text |Cite
|
Sign up to set email alerts
|

Population Pressure on Land Resources in Nigeria: The Past and Projected Outcome

Abstract: Aims: This paper assesses the population pressure on land resources in Nigeria: The past and projected outcome. Study Design: 1967 to 2068 time series data were used. The data sets were resorted to due to lack of complete national data. Place and Duration of Study: Past (1967-2017) and projected (2018-2068) five decades in Nigeria. Methodology: The time series data were obtained from the United Nations Population Division, Department of Economic and Social Affairs, National Population Commiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Nigeria currently has the world's seventh largest population, and it is the second fastest growing after India, so it is expected to overtake India as the third largest by 2050 (Population Reference Bureau, 2018). In their study showed that the mean annual pressure on land resources in Nigeria in the past five decades (1967-2017) was 9.323 hectares per capita, while the projected pressure in the next five decades (2018-2068) was 213.178 hectares per capita (Eririogu et al, 2020). This results implies that about 73.08 percent of the pressure per capita in the past five decades emanated from arable land consumption (6.813ha), while 75.91percent of the pressure is expected to emanate from fossil land in the next projected five decades due to crude oil and mineral resource exploration and exploitation.…”
Section: Understanding Dpsir Framework and Its Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nigeria currently has the world's seventh largest population, and it is the second fastest growing after India, so it is expected to overtake India as the third largest by 2050 (Population Reference Bureau, 2018). In their study showed that the mean annual pressure on land resources in Nigeria in the past five decades (1967-2017) was 9.323 hectares per capita, while the projected pressure in the next five decades (2018-2068) was 213.178 hectares per capita (Eririogu et al, 2020). This results implies that about 73.08 percent of the pressure per capita in the past five decades emanated from arable land consumption (6.813ha), while 75.91percent of the pressure is expected to emanate from fossil land in the next projected five decades due to crude oil and mineral resource exploration and exploitation.…”
Section: Understanding Dpsir Framework and Its Applicationsmentioning
confidence: 99%
“…This results implies that about 73.08 percent of the pressure per capita in the past five decades emanated from arable land consumption (6.813ha), while 75.91percent of the pressure is expected to emanate from fossil land in the next projected five decades due to crude oil and mineral resource exploration and exploitation. This signals a reduction in carrying capacity from 6.4091 hectares per capita to 1.667 hectares per capita (2018-2068) (Eririogu et al, 2020). Moreover, the ability of land for agriculture has deteriorated as population demand on arable land has increased.…”
Section: Understanding Dpsir Framework and Its Applicationsmentioning
confidence: 99%
See 2 more Smart Citations